Design and Characteristic Analysis of Reflux Type Mechanical Hydraulic Hybrid Transmission for Wind Turbines - Fuquan Dai; Yonggang Lin; Yajing Gu; Hongwei Liu; Wenting Chen; Xingchen Zhao (Wind Energy)
ABSTRACT With the development of wind turbines to deep sea, its working environment is more and more severe, which puts higher stability requirements of the transmission chain. A variety of front‐end speed regulation methods have been proposed because this method can improve the reliability of wind turbines by eliminating electrical components with high failure rates. In this paper, referring to the WinDrive, the reflux‐type mechanical hydraulic hybrid transmission (R‐MHHT) front‐end speed regulation structure is proposed based on existing split type mechanical hydraulic hybrid transmission (S‐MHHT). After comparing the power distribution characteristics and speed regulation characteristics of the two structures, the comparison is further carried out at the overall design level of the transmission chain. It is proved by derivation that R‐MHHT has the advantages of lower structural complexity and smaller displacement requirement. In this study a cosimulation model of a 10 MW R‐MHHT wind turbine was built using Simulink and AMEsim. The correctness of theory derivation of R‐MHHT was verified by cosimulation with a slope wind. Moreover, a 23 degrees‐of‐freedom pure torsion model has been established to study the internal characteristics of the R‐MHHT chain. To facilitate the overall modeling, the closed hydraulic system is regarded as a parallel gear transmission. The effects of hydraulic system displacement on frequency and damping of R‐MHHT chain are thoroughly analyzed. The results show that with the increase of pump displacement, the minimum frequency of the transmission chain decreases slightly, and the damping of the first two modes of the transmission chain increases significantly. This shows that the stability of the R‐MHHT chain is improved due to the addition of the hydraulic system.